(untitled) (International Journal on Stereo & Immersive Media, 2025)
Francis Frith (1822–1898) is considered one of the great topographical photographers of the nineteenth century and a pioneer of immersive media for his groundbreaking stereo photography work. In 1856 he began his first of three expeditions to Egypt and the Holy Land, the last of which concluded in 1860. An aspect of his photographic practice was to capture the region using stereo photography, which creates an illusion of a single three-dimensional image from two separate images. Using primary and secondary sources related to Frith’s photographic pursuits and travels in the region, this article focuses on Frith’s technological achievements using stereo photography in Egypt, from his production techniques to the dissemination of his stereo images in his 1862 book, Egypt, Nubia, and Ethiopia. Illustrated by One Hundred Stereoscopic Photographs, Taken by Francis Frith for Messrs. Negretti and Zambra; with Descriptions and Numerous Wood Engravings, by Joseph Bonomi ... and Notes by Samuel Sharpe.